Reassessing the Originality of Tarjumān al-Mustafīd: Dāūd al-Rūmī’s Contributions and the Scholarly Significance of the First Tafsīr in The Archipelago - Muhammad Amin; Yusuf Rahman; Zulkifli (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
Peter Riddell and Salman Harun have conducted studies on the originality of Tafsīr Tarjumān al-Mustafīd. However, their study was based on a limited sample (the 16th and 30th juz), which resulted in the omission of several significant aspects. This study seeks to broaden the scope of research by employing a more comprehensive methodological approach, specifically textual criticism and comparative analysis. Textual criticism is used to assess the authenticity of the text, identify its primary reference sources, and evaluate the interpolations found within the work. Additionally, this study employs comparative analysis by juxtaposing Tarjumān al-Mustafīd with notable classical commentaries, including al-Jalālain, al-Baiḍāwī, and al-Khāzin. Furthermore, an analysis of colophons and variations in writing style is conducted to elucidate the role of each contributor. This study presents three key findings. First, both Riddell and Harun concur that this work is not a translation of al-Baiḍāwī but instead of al-Jalālain. This study aligns with Harun’s assertion that Tarjumān al-Mustafīd is an orally transmitted translation of al-Jalālain, supplemented with quotations from al-Khāzin and additional interpolations, particularly in the 29th and 30th juz, which were primarily influenced by Dāūd al-Rūmī. Secondly, this study reveals that Dāūd al-Rūmī played a crucial role in the preservation and textual modifications of the work, despite its attribution to ʿAbd al-Raʾūf. Third, the scholarly significance of Tarjumān al-Mustafīd  is demonstrated through its role as the first tafsīr in the archipelago to document diverse qirā’āt traditions, reflect the vernacularization of Malay culture, and serve as a vital Qur'ānic guide for the general Muslim populace in 17th-century Aceh.